(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
In the present study, antioxidant activities of aqueous and methanolic fruit extracts of Pritchardia arecina were investigated. The antioxidant properties of the extracts were assessed using 1, 1,-diphenyl-2-picryl-hydrazyl (DPPH) assay and reducing power assay. Both the extracts exhibited significant reducing power which was dose dependent. The IC50 value in DPPH assay was found to be 18 and 27µg/ml for methanolic and aqueous extract respectively. Phytochemical analysis revealed the presence of tannins, steroids, amino acids and carbohydrates. The total phenolic content observed for aqueous and methanolic extracts were 25 and 40 mg gallic acid equivalent per gram of extract respectively.